Decision Support System of Rice Production Needs Rice Milling Unit Case Study of Padangsidimpuan City - Mustafa Parlindungan; Saipul Bahri Daulay; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2015)
The role of food commoditis (particularly rice) since years ago in Indonesia, was so good, as rice is a basic foodstuffs for the majority of Indonesian. Food needs of rice in our country is never recedes, but increased from year to year, in accordance with population growth. The importance of this report was to forecast rice plant production by means of rice plant prediction with monte carlo method to predict the needs of Rice Milling  Unit in the future. The results showed that rice production in 2013 to 2017 was increased so that the availability of Rice Milling Unit in subdistrict of Padangsidimpuan Hutaimbaru was unable to meet grinding rate, therefore steamroller should be created. Keywords: monte carlo , rice milling unit